HEARTS APART: THE IMPACT OF PARENTAL MIGRATION ON THE LIFE OF LEFT-BEHIND FILIPINO ADOLESCENTS - Rendeza, Karen (PEOPLE: International Journal of Social Sciences, 2017)
This descriptive study delved into the impact of parental migration to the academic, emotional, social and spiritual life of left-behind Filipino adolescents. Awareness on the reality of the situation of the left-behinds in different aspects of their life could be of great help to their carers and teachers in creating a meaningful and healthy environment that is facilitative of their growth as persons despite the absence of their biological parent/s. A survey using a researcher’s made questionnaire, mental ability and personality tests as well as interview and the respondents’ scholastic records were utilized in this study. Findings revealed that across the three groups of research participants (those with Overseas Filipino Worker (OFW) father, those with OFW mother, and those with both parents abroad), all of them have good grades in school despite no parent/s assisting them to do their home works and projects plus the additional responsibilities at home for some of them. However, majority of the participants expressed that they feel deeply sad, longing for the physical presence of their parents, though they do not feel rejected and abandoned. For them, it is a tiresome cycle of adjustment every time their parent/s come/s home and then later leave/s them again to work abroad. Prayers continue to bind the Filipino families together despite physical distance. This study concludes that parents should support not just the economic, but also the psychological and the spiritual needs of their left-behind children to help them to cope well with the adversaries of life, thus keeping them away from vices and behavioral problems. Future study shall include more number of participants from different cultures to better see the significance of these findings in many varied family experiences of the adolescent left-behinds.